Estabilidade da polpa de caju congelada obtida com o uso de conservantes, pasteurizada e concentrada - Silva, Virlane Kelly Lima da (2013)
The cashew (Anacardium occidentale, L.) has a great economic importance to the Northeast region, notably for the great acceptance by consumers, both for their sensory properties (color, aroma, flavor, texture) as for its nutritional and functional values. It stands out among the fruit species native to the Northeast because it has high potential for fresh consumption and industrial processing. The cashew and cashew apple juice are important components of the human diet because they are considered a natural source of carbohydrates, carotenoids, vitamins and phenolic compounds, substances with high antioxidant potential, and have attracted the interest of various research groups. This work aimed to study the stability of cashew apple pulp with preservatives, pasteurized and concentrated frozen storage for 12 months, through to chemical, physical-chemical and microbiological analysis. And production of cashew apple nectar and cashew apple sweetened tropical juice and sensorial stability during 360 days of storage of the pulp. The pulps showed no significant interaction for pH, soluble solids, acidity and color coordinated. The pH and soluble solids varied with time but remained within standards legislation. The acidity no change during the storage. The color coordinate set to the cubic model. The parameters vitamin C ranged from 190.65 to 308.45 in the pulp with preservatives, 170.95 to 299.70 in the pulp pasteurized and from 514.68 to 865.42 mg/100g in concentrated pulp, these values very expressive. Dark pigments soluble, brightness, hue*, chroma*, carotenoids, pulp content, total sugar showed significant interaction were assessed by regression with time varying storage except color coordinate b. The concentration of total sugars remained around 10.01 to 13.25% for pulps with preservatives and pasteurized,and to 24 to 27% in the concentrated pulp, which are mostly represented by sugars. The microbiological analyses confirmed the effectiveness of the processing, thermal treatment and concentration in the maintenance of the microbiological quality, once growth of microorganisms was not observed in the product during the storage period. The cashew apple nectars and juices sweetened have good acceptability in all sensory attributes. The frozen pulps cashew with preservatives, pasteurized and concentrated is viable since no significant losses occur in the quality of products.